Wakefield acceleration in planetary atmospheres: A possible source of MeV electrons. The collisionless case. (July 2018) - Arrayás, M.; Cubero, D.; Montanya, J.; Seviour, R.; Trueba, J.L.
Abstract: Intense electromagnetic pulses interacting with a plasma can create a wake of plasma oscillations. Electrons trapped in such oscillations can be accelerated under certain conditions to very high energies. We study the optimal conditions for the wakefield acceleration to produce MeV electrons in planetary plasmas under collisionless conditions. The conditions for the optimal plasma densities can be found in the Earth atmosphere at higher altitudes than 10–15 km, which are the altitudes where lightning leaders can take place.